2008
DOI: 10.1037/0002-9432.78.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Relationship network quality: Adolescent adjustment and perceptions of relationships with parents and friends.

Abstract: Early, mid-, and late adolescents (N = 406) from an ethnically diverse community completed questionnaires describing positive and negative features of relationships with their mothers, fathers, and same-sex best friends. School grades, self-reported adjustment problems, and self-worth differed as a function of both the number of relationships that adolescents described as high on positive features and the number of relationships that adolescents described as high on negative features. Adolescents with relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 21 publications
5
48
0
2
Order By: Relevance
“…The results also revealed, conversely, that high maternal support buffered against the development of adjustment problems from Grade 1 to Grade 2 for children with lack of positive teacher affect. These results support the deficit model of relationships (Laursen & Mooney, 2008), suggesting that a single highquality relationship can buffer against adjustment problems associated with another, low-quality, relationship. Previous studies have shown that teachers may compensate for preschool children's relationship problems with parents and peers (Buyse, Verschueren, & Doumen, 2009;Johnson et al, 2013;M.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The results also revealed, conversely, that high maternal support buffered against the development of adjustment problems from Grade 1 to Grade 2 for children with lack of positive teacher affect. These results support the deficit model of relationships (Laursen & Mooney, 2008), suggesting that a single highquality relationship can buffer against adjustment problems associated with another, low-quality, relationship. Previous studies have shown that teachers may compensate for preschool children's relationship problems with parents and peers (Buyse, Verschueren, & Doumen, 2009;Johnson et al, 2013;M.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, we examined the interactive effects of positive teacher affect for the child and maternal support on child adjustment behaviors after the critical transition to primary school. Consistent with the deficit model (Laursen & Mooney, 2008), we predicted that positive relations with teachers would buffer against adjustment problems associated with low maternal support and that maternal support would buffer against adjustment problems associated with lack of positive teacher affect. The poorest adjustment outcomes were expected for students who received low support from both teachers and parents (Sameroff, 1993).…”
Section: Research Questions and Hypothesessupporting
confidence: 61%
See 3 more Smart Citations